Switch as maintenance to elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil fumarate: week 48 results in a clinical cohort. (10th February 2017) - Perrier, Marine; Charpentier, Charlotte; Peytavin, Gilles; Lê, Minh; Blondel, Louis; Visseaux, Benoit; Joly, Véronique; Pinto, Adriana; Matheron, Sophie; Yazdanpanah, Yazdan; Descamps, Diane; Landman, Roland
Abstract : Objectives: To assess, in a clinical cohort, the efficacy of switching current ART in virologically suppressed patients to elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil fumarate as a single-tablet regimen (STR) using the PCR signal of the plasma viral load (pVL) assay and determination of plasma drug concentration ( C 24 ). Patients and methods: This was an observational single-centre study enrolling antiretroviral-treated patients with pVL <50 copies/mL initiating elvitegravir-based STR. PCRneg was defined as an undetected PCR signal. Results: One hundred and fifty-one patients were enrolled. At STR baseline, the median time since first ART and time of virological suppression were 5 years (IQR 3–9) and 24 months (IQR 9–44), respectively. By week (W) 48, 26 (17%) of the patients had discontinued STR due to adverse events. The proportion of patients maintaining pVL <50 copies/mL on treatment was 98%, 96%, 93% and 97% at W12, W24, W36 and W48, respectively. Five patients (3.3%) experienced a virological failure and emergence of resistance was observed in two of them with the selection of M184V and N155H mutations. At baseline, W12, W24, W36 and W48, 70%, 57%, 72%, 61% and 74% of the patients with pVL <20 copies/mL had a PCRneg, respectively. The median elvitegravir plasma C 24 value was 648 ng/mL (IQR 348–989; n  =   237), with 84% of elvitegravir C 24 values >45 ng/mL, the protein-adjusted IC95 . Conclusions: In this clinical cohort of virologically suppressed patients switching to STR, most subjects had adequate elvitegravir C 24 values with a high proportion maintaining virological suppression with no residual viraemia until W48.